Вибір ідеї та фінансування стартапів - Болтянська, Лариса Олексіївна; Boltianska, Larysa; Андрєєва, Л.О.; Лисак, Оксана Іванівна; Lysak, Oksana (Мелітополь: ТДАТУ, 2021)
Ukr: Сучасні ринкові умови надають можливість перетворити бізнес-ідею в ринковий продукт. В статі зазначені аспекти пошуку та методи вибору ідеї. Розкрито можливі джерела фінансування українських стартапів, визначені переваги та недоліки співпраці стартапера з інвестором. Наведено рейтинг найбільш вдалих та перспективних до реалізації проектів, що отримали найбільший обсяг інвестицій для реалізації своїх бізнес-ідей.

Eng A well-formed idea can determine the starting activity in the future of a capable entrepreneur, but in the future to continue the business requires updated ideas. The essence of the idea is formed under the influence of many internal human motives, external environmental factors, as well as the presence of some initial knowledge of the future entrepreneur. Especially important in this direction is the presence of a circle within which you can determine the source of a new idea, based on the scope of activities, the ability to invest equity and / or debt capital, the prospect of return on financial resources. Given the growing pace of technological progress, we believe that it is best to choose a business idea, giving preference to the most original proposal, even if it is unclear how to make money on such activi ties. It is especially important to focus on a favorite thing, or even a hobby where there is experience of activity. Every year in Ukraine the number of innovative ideas and progressive people who are ready to implement these ideas grows. However, the most original idea does not always survive in the market and finds funding for implementation. The main thing for a startup is to determine which investor is needed: who invests money to make their own profit or who helps manage the project. That is why the choice of an investor depends on the end result of the startup: the sale of a well established business or activity in the established enterprise. The conceptual task of a startup in general is to determine the main purpose of their own business, as well as awareness of the directions and resources to achieve them. This provides an opportunity to determine a detailed algorithm of actions for the success of the goals. The number of innova tive startups is growing every year, the number of progressive and creative people who want to realize their idea is increasing, but to move along the chain "from idea to first profits" requires a lot of effort, skills, knowledge, desire to constantly learn, develop and be ready to responsibility for the results.
Keywords: бізнес-ідея; грантове фінансування; бізнес-ангел; вен чурні капітал; бізнес-інкубатор; фінансування; інвестор; джерела пошуку ідеї; стартап; business idea; startup; sources of idea search; financing; investor; business incubator; venture capital; business angel; grant financing.